Mindfulness-based couple interventions: a systematic literature review - Winter, Friederike; Steffan, Antonia; Warth, Marco; Ditzen, Beate; Aguilar-Raab, Corina (Family process, 2021)
Over the past decades, mindfulness-based interventions have been shown to improve individual health and well-being in clinical and nonclinical settings. More recently, secular contemplative trainings were adapted to the couple context as research showed satisfying couple relationships to be one of the strongest predictors of physical and mental health. Mindfulness-based interventions hence seem to be a promising treatment in couple counseling and therapy in both clinical and nonclinical settings. Therefore, we conducted a systematic review to provide an overview of the emerging literature in the field of mindfulness-based interventions for couples and other dyads. Overall, sixteen studies met the inclusion criteria. To summarize the heterogeneous quantitative literature regarding individual outcomes, mindfulness interventions for couples seem to increase mindfulness, self-compassion, well-being, and quality of life. Additionally, we found initial evidence of beneficial effects on relieving psychopathological symptoms and psychobiological stress measures. Measures of relationship quality were the predominant dyadic outcome. Based on these studies, we cautiously conclude that mindfulness trainings can enhance relationship quality. Practitioners should be aware that mindfulness-based interventions for couples can potentially improve the perceived relationship quality between partners and the individual burden. Future studies should expand the field, particularly with regard to other contemplative practices for couples such as compassion interventions.